The effectiveness of weight-belts during multiple repetitions of the squat exercise - Lander, J. E.; Hundley, J. R.; Simonton, R. L. (Medicine & Science in Sports & Exercise, 1992)
Lander et al (1) examined the effects of the use of weight belts on muscle activity, intra-abdominal pressure (IAP), and ground reaction forces during multiple repetitions of the squat exercise. Five experienced male trainees were examined; all subjects could squat a mean 8 RM of 1.6 times their body weight. Two conditions were examined: no weight belts and a weight belt. Squats were performed for 8 repetitions using a 8 RM load. All performances were filmed using a Locam high speed 16-mm camera. Vertical, anteroposterior, and mediolateral forces were measured using a Kistler force platform. Intra-abdominal pressure was measured using a balloon catheter inserted in each subject's rectum. EMG signals from the external obliques, erector spinae, vastus lateralis, and biceps femoris were measured. Kinematic data was generated from the digitized film. The lift was divided into 6 phases; the downward phase of the squat was P1-P3, and the upward phase was P4-P6.